Characterization of mesoporosity in ceria particles using electron microscopy - Shih, S; Herrero, P; Li, G; Lozano-Perez, S; Chen, C (2011)
The geometry and three-dimensional (3D) morphology of the ceria particles synthesized by spray pyrolysis (SP) from two different precursors-cerium acetate hydrate and cerium nitrate hydrate (CeA and CeN ceria particles)-were characterized by transmission electron microscopy and electron tomography. Results were compared with surface area measurements, confirming that the surface area of CeA ceria particles is twice as large as that of CeN ceria particles. This result was supported by 3D microstructural observations, which have revealed that CeA ceria particles contain open pores (connected to surfaces) and closed pores (embedded in particles), while CeN ceria particles only contained closed pores. This experimental result suggests that the type of porosity is controlled by the precursors and could be related to their melting temperature during the heating process in SP. © 2011 Microscopy Society Of America.